M2(H2O)[μ10-C6H2(COO)4] (M = Ba2+, Pb2+) - Two Isotypic Three-Dimensional Coordination Polymers with a Layer-like Separation between Anions and Cations - Köferstein, Roberto; Robl, Christian (Zeitschrift für anorganische und allgemeine Chemie (1950), 2015)
Monoclinic single crystals of Ba2(H2O)[μ10‐C6H2(COO)4] (1) and Pb2(H2O)[μ10‐C6H2(COO)4] (2) were obtained using the silica gel method [space group C2/c (no. 15), Z = 4; 1: a = 780.89(4), b = 1756.19(8), c = 914.80(5) pm, β = 114.512(5)°; 2: a = 756.70(10), b = 1772.8(2), c = 890.2(2) pm, β = 113.590(10)°]. There are two crystallographically independent M2+ ions (M = Ba, Pb). M(1) is surrounded by eight carboxylate oxygen atoms and one water molecule forming a tricapped trigonal prism. M(2) is coordinated by ten carboxylate oxygen atoms in the shape of a tetracapped octahedron. The connection between the M(1) and M(2) polyhedra leads to infinite layers parallel to (010), which are linked by [C6H2(COO)4]4– anions to form a three‐dimensional framework. The [C6H2(COO)4]4– anion adopts a μ10 coordination mode. Compound 1 reveals short Ba–Ba contacts of 426.46(2) pm, whereas the Pb–Pb distance of 411.01(6) pm in 2 is larger than twice the van der Waals radius.